Exogenous Citrulline and Glutamine Contribute to Reverse the Resistance of Salmonella to Apramycin - Yong, Yan; Zhou, Yanhong; Liu, Kexin; Liu, Guochang; Wu, Liqin; Fang, Binghu (Frontiers in Microbiology, 2021)
Antibiotic resistance is an increasing concern for human and animal health worldwide. Recently, the concept of reverting bacterial resistance by changing the metabolic state of antibiotic-resistant bacteria has emerged. In this study, we investigated the reversal of Apramycin resistance in Salmonella. First, non-targeted metabonomics was used to identify key differential metabolites of drug-resistant bacteria. Then, the reversal effect of exogenous substances was verified in vivo and in vitro. Finally, the underlying mechanism was studied. The results showed that the metabolites citrulline and glutamine were significantly reduced in Apramycin-resistant Salmonella. When citrulline and glutamine were added to the culture medium of drug-resistant Salmonella, the killing effect of Apramycin was restored markedly. Mechanistic studies showed that citrulline and glutamine promoted the Tricarboxylic acid cycle, produced more NADH in the bacteria, and increased the proton-motive force, thus promoting Apramycin entry into the bacterial cells, and killing the drug-resistant bacteria. This study provides a useful method to manage infections by antibiotic-resistant bacteria.